Cortical and thalamic hyper-perfusion in non-convulsive status epilepticus. Relationship between perfusion CT patterns and Salzburg EEG criteria. (November 2021) - Giovannini, Giada; Malagoli, Marcella; Turchi, Giulia; Miani, Alice; Orlandi, Niccolò; Vaudano, Anna Elisabetta; Meletti, Stefano
Highlights: Perfusion CT could support the diagnosis of focal NCSE. Cortical plus thalamus hyper-perfusion is highly suggestive of focal NCSE. Focal cortical hyper-perfusion and ictal activity showed good spatial concordance. Continuous focal ictal patterns especially determine hyper-perfusion. Abstract: Introduction: Status epilepticus (SE) is a neurological emergency and in particular nonconvulsive SE (NCSE) represents a diagnostic challenge. To improve clinical decision-making, cerebral perfusion-computed tomography (PCT) has been shown as a helpful tool to support the diagnosis of focal NCSE. Materials and methods: This is a monocentric retrospective study. Among the 602 cases of SE observed between September 2013 and April 2020 we included 21 patients that were studied with PCT. The perfusion maps were first visually analysed then a quantitative analysis (by regions of interest, ROI) was obtained. For each patient, the diagnostic EEG was reviewed and classified in accordance to the Salzburg Criteria for NCSE (SCC) as definite (D-NCSE) and possible (P-NCSE). Finally, we analysed the relationship between PCT and EEG patterns. Results: Hyper-perfusion was observed in 18 patients (86%), while in the remaining 3 (14%) a normo-perfused pattern was present. Hyper-perfusion was observed in 14 of the D-NCSE group (88%) and in the two patients with a P-NCSE (100%). No one among the patients with a P-NCSE had a thalamic hyper-perfusion, while among the 6 patients with continuous sustained epileptiform discharges > 2.5 Hz (pattern 1 of SCC), 4 (67%) showed cortical plus thalamic hyper-perfusion. Conclusions: PCT could facilitate the differential diagnosis and speed-up the diagnostic process of NCSE in emergency situations. Finding cortical multi-lobar hyper-perfusion, especially if present together with homolateral thalamic hyper-perfusion in a patient with an acute-onset of motor/sensory/language deficits is highly suggestive for the presence of NCSE and is particularly related to continuous/sustained ictal patterns.